Damage modelling of carbon fibre composite crush tubes: numerical simulation and experimental validation of drop weight impact - Sommer, DE; Thomson, D; Falcó, O; Quino, G; Cui, H; Petrinic, N (Elsevier, 2022)
Angle-ply carbon fibre reinforced polymer (CFRP) crush tubes were tested in drop weight impact experiments. High-fidelity computational modelling of the dynamic impact response was performed using explicit finite element analysis in LS-DYNA. Ply-by-ply and fibre-aligned meshing was used for the composite lamina wherein the intralaminar damage was treated with a 3D rate- and pressure-dependent continuum damage mechanics (CDM) model, implemented as a user material. Delamination was modelled using cohesive tiebreak contacts to deal with the mis-matched nodes caused by the use of a structured, fibre-aligned mesh. The material aligned meshing scheme was shown to be required to capture the intralaminar splits observed in the ±45° plies. The numerical predictions showed excellent correlation with experimental measurements in terms of both the damage mechanisms and macroscopic material behaviour of the drop weight. In the simulation, interlaminar friction between delaminated plies seemed to be a main contributor of energy dissipation. Parameter sensitivity analysis showed that the interaction between the delamination fracture energy and friction can substantially influence the results and stable crushing load, in particular. For the scenario studied here, a regular structured mesh (unaligned) was shown to be insufficient for simulating realistic crack paths despite producing reasonable predictions of the force–displacement and absorbed energy.